What was observed by Julius Planer in 1861? - Lisetski, L. (Condensed Matter Physics, 2010)
In 1861 Julius Planner published a paper in which he described his observations of selective light refection in monotropic cholesteric liquid crystal phase of cholesteryl chloride that he synthesized. We repeat his experiments and report in modern interpretation what indeed was observed by Planer at that time. У 1861 р. Юліус Планер опублікував статтю, в якій він описав свої спостереження селективного відбивання світла в монотропній холестеричній фазі синтезованого ним холестерилхлориду. Повторено його експерименти та повідомлено в сучасній інтерпретації, що в дійсності спостерігав Планер у той час.